Chronic stress improves NO- and Ca2+flux-dependent vascular function: a pharmacological study - Bruder-Nascimento, Thiago [UNESP]; Campos, Dijon Henrique Salome [UNESP]; Cicogna, Antonio Carlos [UNESP]; Cordellini, Sandra [UNESP] (Arquivos Brasileiros Cardiologia, 2015)
Background: Stress is associated with cardiovascular diseases.Objective: This study aimed at assessing whether chronic stress induces vascular alterations, and whether these modulations are nitric oxide (NO) and Ca2+ dependent.Methods: Wistar rats, 30 days of age, were separated into 2 groups: control (C) and Stress (St). Chronic stress consisted of immobilization for 1 hour/day, 5 days/week, 15 weeks. Systolic blood pressure was assessed. Vascular studies on aortic rings were performed. Concentration-effect curves were built for noradrenaline, in the presence of L-NAME or prazosin, acetylcholine, sodium nitroprusside and KCl. In addition, Ca2+ flux was also evaluated.Results: Chronic stress induced hypertension, decreased the vascular response to KCl and to noradrenaline, and increased the vascular response to acetylcholine. L-NAME blunted the difference observed in noradrenaline curves. Furthermore, contractile response to Ca2+ was decreased in the aorta of stressed rats.Conclusion: Our data suggest that the vascular response to chronic stress is an adaptation to its deleterious effects, such as hypertension. In addition, this adaptation is NO-and Ca2+-dependent. These data help to clarify the contribution of stress to cardiovascular abnormalities. However, further studies are necessary to better elucidate the mechanisms involved in the cardiovascular dysfunction associated with stressors.

Fundamento: Estresse está associado com complicações cardiovasculares. Objetivos: O objetivo do presente estudo foi avaliar se o estresse crônico induz alterações vasculares, e se essas alterações são dependentes de óxido nítrico (NO) e Ca2+. Métodos: Ratos machos Wistar com 30 dias de idade foram separados em 2 grupos: controle (C) e Estresse (St). Utilizou-se estresse crônico de imobilização por 1 hora/dia, 5 dias/semana, 15 semanas. Pressão arterial sistólica foi avaliada. A função vascular foi avaliada em anéis aórticos. Curvas de concentração-efeito foram realizadas para noradrenalina, na presença de L-NAME ou prazosina, cloreto de potássio (KCl), acetilcolina e nitroprussiato de sódio. Também foi efetuado um estudo para avaliação para fluxo de Ca2+. Resultados: Estresse crônico induziu hipertensão e resposta vascular diminuída para noradrenalina e KCl e aumentada para acetilcolina. A pré-incubação com L-NAME eliminou a diferença para noradrenalina. A resposta contrátil vascular para Ca2+ foi reduzida em animais estressados. Conclusão: Nossos dados sugerem que a resposta vascular ao estresse crônico seria uma adaptação aos efeitos deletérios do estresse, incluindo a hipertensão. Além disso, esses mecanismos adaptativos dependem de liberação de NO e fluxo de Ca2+. Esses resultados ajudam a esclarecer os mecanismos envolvidos nas alterações cardiovasculares associadas ao estresse. Entretanto, mais estudos são necessários para a melhor compreensão desses mecanismos.
Estresse crônico melhora a função vascular dependente de NO e fluxo de Ca2+: um estudo farmacológico
Keywords: Stress physiological / physiopatology; Hypertension; Nitric oxide / physiology; Rats; Vasoconstrictor agents / pharmacology; Estresse fisiológico / fisiopatologia; Hipertensão; Óxido nítrico / fisiologia; Ratos; Vasoconstritores / farmacologia